VARIASI KETINGGIAN SUMBER AIR TERHADAP TEKANAN DAN DEBIT AIR POMPA HIDRAM - Eka Putra, Ismet; Wardianto, Dedi; Pratama, Agung (ITP Press, 2024)
The hydram pump is a water pump that is energy efficient and environmentally friendly. The hydram pump is an appropriate technology in the field of pumping that uses water momentum (water hammer) to raise water, so the hydram pump is one of the water pumps that does not use fuel and electricity. Much research has been carried out regarding hydram pumps, but there is still much that needs to be studied so that knowledge about hydram pump planning is better. The effective performance of a hydram pump is influenced by several parameters, including drop height, pipe diameter, pipe type, characteristics of the waste valve, length of the inlet pipe and length of the pipe on the waste valve. The water source comes from the Unand Dam River flow, with variations in the height of the water source, namely 0.7m, 1.3m and 1.9m. with water flowing using an inlet pipe with a pipe diameter of 2 inches with a pipe length of 8 meters, and an outlet water pipe with a diameter of 1 inch with a height of 8 meters. The first test with a water source height of 0.7m obtained an inlet water pressure of 1.1 bar and an outlet water pressure of 1bar, with an outlet water pipe height of 8 meters which resulted in an outlet water discharge of 0.037 (L/second). In the second test with a water source height of 1.3 m, the inlet water pressure was 1.3 bar and the outlet water pressure was 1.2 bar, with an outlet water pipe height of 8 meters which resulted in an outlet water discharge of 0.071 (L/second). And in the third test with a water source height of 1.9m, the incoming water pressure was 1.4 bar and the outgoing water pressure was 1.3 bar, with an outgoing water pipe height of 8 meters which resulted in an outgoing water discharge of 0.091 (L/second).